2020
DOI: 10.1055/s-0039-3401380
|View full text |Cite
|
Sign up to set email alerts
|

The Serially-Operated Essex-Lopresti Injury: Long-Term Outcomes in a Retrospective Cohort

Abstract: Objective The main aim of this article is to report 10-year outcomes after Essex-Lopresti injury (ELI). Study Design Retrospective case series. Two level I trauma centers and one associated community hospital from 2003 to 2016. Patients Sixteen patients who sustained an ELI and were treated at one of our three regional hospitals. Intervention Initially, 4 patients (25%) were treated nonoperatively by immobilization and 12 patients (75%) were treated operatively. Proximal surgery included radial head open reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
(62 reference statements)
0
4
0
Order By: Relevance
“…Our initial search revealed 47 eligible articles ( 6 , 7 , 11 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ) ( Fig. 1 ), of which 27 were case reports and 20 were case series.…”
Section: Resultsmentioning
confidence: 99%
“…Our initial search revealed 47 eligible articles ( 6 , 7 , 11 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ) ( Fig. 1 ), of which 27 were case reports and 20 were case series.…”
Section: Resultsmentioning
confidence: 99%
“…While we believe a radial head, replacement adds to the stability of the forearm, in our case damage to the proximal radius after loosening of the primary RH arthroplasty precluded the reliable use of a revision arthroplasty. The limited available evidence suggests that satisfactory results can be achieved by IOM reconstruction without the use of a RH arthroplasty [2,19].…”
Section: Resultsmentioning
confidence: 99%
“…20 Addressing the injury to the radial head alone by osteosynthesis or arthroplasty fails to restore forces across the forearm, which can lead to radiocapitellar degeneration, failure of osteosynthesis, or failure of radial head arthroplasty through loosening, dislocation, or capitellar erosion. 21,22 Verhiel et al 23 reported 32 revision procedures in 16 patients with longitudinal instability lesions treated with radial head arthroplasty over a ten-year follow-up.…”
Section: Discussionmentioning
confidence: 99%